How does an individual's default behavior on an online peer-to-peer lending platform influence an observer's default intention? - Ming Feng Tang; Mei Mei; Cuiwen Li; Xingyang Lv; Xushuang Li; Lihao Wang (Financial Innovation, 2020)
Previous studies indicate that individuals' default behaviors on online peer-to-peer (P2P) lending platforms greatly influence other borrowers' default intentions. However, the mechanism of this impact is not clear. Moreover, there is scarce research in regard to which factors influence the relationship between an individual's default behavior and an observer's default intention. These important questions are yet to be resolved; hence, we conducted two experiments using the scenario-based research method, focusing on Chinese online P2P lending platforms. Our results indicate that an individual's default behavior can trigger an observer's default intention as a result of the imperfect punitive measures as they currently exist on Chinese online P2P lending platforms. Both the observer's moral disengagement level and pragmatic self-activation level serve as mediating variables. In situations where an observer knows an individual's default behavior, the level of intimacy between the defaulter and observer positively affects the relationship between their default behavior and intention. The intimacy level also positively influences the relationship between the individual's default behavior and the two mediator variables. Based on the findings, we provide management suggestions in the context of online P2P lending. Our study sets a foundation for future research to utilize other methods to extend the present research findings to other regions and domains.
Keywords: 650; Online P2P lending; Individual default behavior; Observer default intention; Moral disengagement; Pragmatic self-activation